SISTEM PEMERINTAHAN PRESIDENSIAL DI INDONESIA PRESPEKTIF FIQH SIYASAH DUSTURIYAH - Astri Wulandari; Zainuddin Zainuddin (Institut Agama Islam Negeri Batusangkar, 2021)
This study discusses the review of Islamic Constitutional Law on presidential government systems in Indonesia. This type of research is library research in which materials are collected through books, laws and journals related to research. The method used is a normative legal research method. Theories used are power theory, authority theory, trias politica theory and tanfidziyyah sulthah theory. From the results of the research conducted by the author, it can be concluded that based on the Indonesian constitution namely the 1945 Constitution in Article 4 paragraph (1) the power of the President includes executive, legislative and judicial powers. In a presidential government system the President is not only the head of state but also the head of government. Based on the Sulfah tanfidziyyah review of the power of the head of state in the presidential system in Indonesia, namely the power of the head of state in the presidential government system does not conflict with Islamic governance and Islamic law because in the Fiqh Siyasah Dusturiyah or the Khalifah Islamic State Constitutional Law covers all power, both as head of state, head of state government, legislature, judiciary and head of religion. It's just that presidential power in the Presidential system does not include as head of religion.